Enhancing Short Story Reading Skills Using Multiple Strategies: Google Form-Based Teaching Materials Supported by Online Scientific Articles - Welsi Damayanti; Elmustian Elmustian; Zamri Mahamod; Rozaiman Makmun; Gamal Abdul Naser Zakaria; Abdul Razak (Badan Pengembangan dan Pembinaan Bahasa, 2026)
This study aims to describe: 1) the results of the pre-test of prophetic short story reading skills; 2) the learning process of prophetic short story reading skills using innovative strategies based on Google Forms integrated with online journal scientific articles; 3) the results of the post-test of prophetic short story reading skills; 4) the role of innovative strategies in improving prophetic short story reading skills. This study uses a quantitative method through a single short case study through a quasi-experiment on new students of the Language and Arts Education Study Program, Universitas Pendidikan Indonesia in the 2024/2025 academic year. The study population was 33 students who took the pre-test, learning activities, and post-test. 31 students were designated as samples. Pre-test and post-test data on prophetic short story reading skills were collected using test instruments. Learning procedure data were collected using observation guidelines. Pre-test and post-test data were each analyzed using a one-sample t-test. Pre-test data analysis used a relatively low mean expectation while post-test data analysis used a relatively high mean expectation. The comparison of pre-test and post-test data was analyzed using a paired sample t-test procedure to determine the role of innovative strategies in improving prophetic short story reading skills. The results of the study: 1) the pre-test mean was only 39.87 (49.84%); 2) the learning procedure was carried out according to plan; 3) the post-test mean was 64.97 (81.21%: A); 4) innovative strategies were able to improve prophetic short story reading skills. Abstrak Penelitian ini bertujuan untuk mendeskripsikan: 1) hasil pre-test kemampuan membaca cerita pendek profetik; 2) proses pembelajaran keterampilan membaca cerita pendek profetik dengan strategi inovatif berbasis Google Forms yang terintegrasi dengan artikel ilmiah jurnal online; 3) hasil post-test kemampuan membaca cerita pendek profetik; 4) peran strategi inovatif dalam meningkatkan keterampilan membaca cerita pendek profetik. Penelitian ini menggunakan metode kuantitatif melalui studi kasus tunggal singkat melalui eksperimen kuasi terhadap mahasiswa baru Program Studi Pendidikan Bahasa dan Sastra, Universitas Pendidikan Indonesia pada tahun akademik 2024/2025. Populasi penelitian adalah 33 mahasiswa yang mengikuti pre-test, kegiatan belajar, dan post-test. 31 mahasiswa ditetapkan sebagai sampel. Data pre-test dan post-test tentang keterampilan membaca cerita pendek profetik dikumpulkan dengan menggunakan instrumen tes. Data prosedur pembelajaran dikumpulkan dengan menggunakan pedoman observasi. Data pre-test dan post-test masing-masing dianalisis menggunakan uji-t satu sampel. Analisis data pre-test menggunakan ekspektasi rata-rata yang relatif rendah sedangkan analisis data post-test menggunakan ekspektasi rata-rata yang relatif tinggi. Perbandingan data pre-test dan post-test dianalisis menggunakan prosedur t-test sampel berpasangan untuk menentukan peran strategi inovatif dalam meningkatkan keterampilan membaca cerita pendek profetik. Hasil penelitian menunjukkan: 1) rata-rata pre-test hanya 39.87 (49.84%); 2) prosedur pembelajaran dilakukan sesuai rencana; 3) rata-rata post-test adalah 64.97 (81.21%:A); 4)strategi inovatif mampu meningkatkan kemampuan membaca cerita pendek profetik.